THE EFFECT OF “REACH” COMMUNICATION (RESPECT, EMPATHY, AUDIBLE, CLARITY, HUMILITY) TOWARD THE CARING BEHAVIOR OF NURSES IN TUBAN - Martianawati; Putri Ryandini, Tiara; Safa’ah, Nurus; Pitaloka, Dyah (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. Caring behavior is influenced by several factors, one of which is communication. Effective communication good will improve the good relationship between a nurse with the client. Caring behavior is an effort nurses make to be close to clients and understand what clients are doing so that nurses can carry out nursing care effectively. Place according to the problems experienced by the client. The study amis to analyze the effect of reach communication and the caring behavior of nurses toward patients in Tuban. Method. The study used a pre-experimental design with a one-group pre post-test design. The sampling method used is simple random sampling with 27 respondents and questionnaires. The sample in this study were all nurses and medical personnel who had communicated with patients at the Tuban. To avoid sample deviation, inclusion and exclusion criteria were found. Result & Analysis. Data analysis was undertaken using Wilcoxon Statistical tests. The results of the statistical test obtained asymp. Sig. (2-tailed) p= 0.001 where the value of p < (0.05<0.05) the hi is accepted, meaning that there is an influence of the REACH communication method (respect, empathy, audible, clarity, humility) on caring behavior in the public health center. Discussion. Nurses should increase reach communication when meeting patients to increase the caring behavior of nurses, doctors, and midwives.